Polarization formula and polarization inequality for $(p,q)$-linear maps - Vasylyshyn, T.V.; Zagorodnyuk, A.V. (Carpathian Mathematical Publications, 2009)
It is proved an analogues of polarization formula and polarization inequality and Martin's formula for $(p,q)$-linear maps on normed spaces.